2016
DOI: 10.1007/s00270-016-1443-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Using 100–300 Versus 300–500 μm Microspheres for Symptomatic Patients Due to Enlarged-BPH Prostates

Abstract: Both 100-300 and 300-500 μm microspheres are safe and effective embolic agents for PAE to treat LUTS-related to BPH. Although functional and imaging outcomes did not differ significantly following use of the two embolic sizes, the greater incidence of adverse events with 100-300 μm microspheres suggests that 300-500 μm embolic materials may be more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 18 publications
2
40
0
3
Order By: Relevance
“…In a small-scale non-randomized comparative study with 15 patients in each arm, Embosphere microspheres of size 100–300 μm and size 300–500 μm were compared for use in PAE for BPH. Although there was no significant difference in functional and imaging outcomes between the two groups, there was a greater incidence of adverse events in the group of smaller particles [14]. In the current study, in which tris-acryl microspheres of size 100 to 300 μm were used, embolization-related complications did not occur, suggesting that it may be safe to use smaller sized microspheres.…”
Section: Discussionmentioning
confidence: 55%
“…In a small-scale non-randomized comparative study with 15 patients in each arm, Embosphere microspheres of size 100–300 μm and size 300–500 μm were compared for use in PAE for BPH. Although there was no significant difference in functional and imaging outcomes between the two groups, there was a greater incidence of adverse events in the group of smaller particles [14]. In the current study, in which tris-acryl microspheres of size 100 to 300 μm were used, embolization-related complications did not occur, suggesting that it may be safe to use smaller sized microspheres.…”
Section: Discussionmentioning
confidence: 55%
“…In conclusion, both studies (45,47) have suggested that larger particles tend to perform slightly better, but studies are heterogeneous, and data are yet not enough.…”
Section: Embolization Particlesmentioning
confidence: 90%
“…Goncalves et al (45) found minor adverse events in patients treated with smaller microspheres. From 3 to 12 months, the smaller particles size revealed a lower regrowth rate in prostate size.…”
Section: Embolization Particlesmentioning
confidence: 97%
See 1 more Smart Citation
“…Early enthusiasm in the procedure was tempered by variable clinical and technical success rates. [5][6][7][8][9] These initial shortcomings were subsequently overcome by more standardization of techniques, 10,11 and better understanding of patient selection and arterial anatomy. 3,7,[12][13][14] Utilizing this refined anatomical and procedural expertise, the goal of this article is to provide a standardized approach to PAE to overcome technical challenges described in the literature.…”
mentioning
confidence: 99%